Strategi Digital Marketing untuk Meningkatkan Penjualan UMKM Melon Golden dari Kota Cilegon melalui Penguatan SDM dan Ekspansi Bisnis Internasional - Jelita Miranti (Journal of Management and Social Sciences, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, including Melon Golden, play a crucial role in the nation's economy. With a significant contribution to GDP and employment absorption, the development of MSMEs through the utilization of technology, particularly digital marketing, is key to expanding markets and enhancing competitiveness. This study aims to analyze the impact of digital marketing on the sales of Melon Golden, as well as identify the digital marketing strategies used and the challenges in its implementation. The method used is a descriptive study with a qualitative approach, conducted at the MSME Melon Golden in Cilegon, Banten. The results show that digital marketing has made a significant contribution to increasing sales by leveraging social media platforms such as Instagram, Facebook, and WhatsApp. The main challenges faced are limited technological understanding and increasing business competition. Strengthening Human Resources (HR) capacity in digital marketing is essential to improving operational efficiency and expanding into international markets. International business expansion strategies, such as product development and promotions tailored to the global market, also offer great opportunities for Melon Golden to increase sales and introduce products to international markets. This study provides valuable insights for MSMEs in addressing challenges and seizing opportunities in the digital era.